The given information can be represented graphically as

Here, AD ⊥ *l*, CF ⊥ *l* and BE ⊥ *l*

AD || CF || BE

In ∆ABE, CG || BE (CF || BE)

And C is the mid-point of AB

Thus, by converse mid-point theorem, G is the mid-point of AE

In ∆ADE, G is the mid-point of AE and GF || AD (CF || AD)

Thus, the converse of mid-point theorem, F is the mid-point of DE.

In ∆CDF and ∆CEF

DF = EF (F is the mid-point of DE)

CF = CF (common)

∠CFD = ∠CFE (Each 90° since F ⊥ *l*)

∴ DDF ≅ DCEF (SAS congruence criterion)

⇒ CD = CE (C.P.C.T)

Hence proved

Hope! This will help you.

Cheers!